Pengaruh Sudut Sudu Pengarah Terhadap Turbin Darrieus Untuk Pembangkit Tenaga LIstrik DI Irigasi Bendungan - Antonius F A Silaen (MAJALAH TEKNIK SIMES, 2018)
The Darrieus turbine consists of one or more long darrieus blades that traces imaginary cylindrical forces such as screw threads. Darrieus aerfoil blades give a reaction force that can attract it faster than the fluid flow itself. This test is carried out irrgation streams Sengkuang Village South Seluma District where the flow rate of water 0,9 m/s. The results obtained in this study were Darrieus Turbine without guide angle at water flow velocity (v) 0,9 m/s, torque coefficient (CT) = 78.80, Turbine efficiency (nt) = 46.847 %, rotation (n) the turbine power (PT)= 43.565 watt. Darrieus turbine uses a steering angle 300 at the velocity of water velocity (v)= 0,9 m/s. the torque coefficient (CT)= 94.32. turbine efficiency (nt)= 27.575%, round 95 Rpm and turbine power (PT)= 43.565 watt. Darrieus Turbine uses 450 directed angle at water flow velocty (v)= 0.9 m/s, torque coefficient (CT)= 95.52, turbine efficiency (nt) = 80.583%, round (n) = 105 Rpm and Turbine Power (PT)=43.565 Watt.